Distribution of pharmacy deserts and its association with digital divide and residential redlining across the United States - Giovanni Catalano; Selamawit Woldesenbet; Timothy M. Pawlik (PLoS ONE, 2025)
Background Recent pharmacy closures across the US has increased the number of communities characterized as “pharmacy deserts.” Residential segregation and structural economic disinvestment including the digital divide may exacerbate inequities related to pharmacy access. Methods In this cross-sectional study, pharmacy deserts were defined at the census tract level and their distribution was analyzed relative to the digital divide index (DDI) and residential redlining using multivariate logistic regression. Results Overall, 3,105 (3.72%) census tracts were classified as pharmacy deserts comprising more than 10 million inhabitants (n = 10,215,249). Pharmacy deserts were more often Black (n = 398, 13% vs. n = 6142, 7.6%), Hispanic (n = 597, 19.0% vs. 7662, 9.5%), or American Indian and Alaska Native (n = 82,14.0% vs. n = 113, 0.1%) segregated communities (all p < 0.001). Census tracts with a high DDI (OR 6.94, 95%CI 5.82–8.32; p < 0.001; E-value = 4.70) had a higher likelihood of being a pharmacy desert versus low DDI areas. Furthermore, census tracts experiencing high residential redlining had a twofold increased risk of being pharmacy deserts (OR 2.18, 95%CI 1.90–2.50; p < 0.001; E-value = 2.31). Conclusions Understanding how socioeconomic and infrastructure factors influence access to pharmacies is crucial to reduce health inequities. Efforts should be made to ensure equitable access to pharmacy services, especially for underserved populations in both rural and urban settings.